Global religious and secular dynamics : the modern system of classification - Casanova, José (Brill research perspectives., 2019)
"Global Religious and Secular Dynamics offers a global historical perspective that integrates European theories of modern secularization and competing theories of global religious revival as interrelated dynamics. In the first section Casanova examines the emergence of the modern religious/secular binary system of classification within a critical review of Émile Durkheim's and Max Weber's divergent theories of religion. The modern system of classification is contrasted with the pre-axial one, in which all reality was organized according to the binary sacred/profane, and with the post-axial one, which was organized according to the binary transcendent/immanent. The second and third sections contrast the internal European road of secularization without religious pluralization with the external colonial road of global intercultural and religious encounters, particularly in Asia, that led to the global system of religious pluralism. The final section examines the contemporary intertwinement of religious and secular dynamics through the globalization of the immanent frame and the expansion of global denominationalism".